Effectiveness of laughter therapy versus humour therapy on quality of life among individuals diagnosed with type 2 diabetes mellitus - P. WALTER JAISINGH,; S. VIJAYALAKSHMI,; R. VIJAYARAGHAVAN, (International Journal of Pharma and Bio Sciences, 2019)
Diabetes mellitus is metabolic chronic diseases, causes many complications and results in poor health and quality of life. The studies have shown that improvement in quality of life results in better self-management skills of diabetes patients. Diabetes diagnosed individuals are benefited with laughter therapy and humour therapy. However, limited studies were conducted on efficacy of these therapies, hence study was conducted to find out the effectiveness of laughter therapy versus humour therapy on quality of life among individuals diagnosed with type 2 diabetes mellitus. A true experimental design with simple random sampling was used in the study. The participants were randomly allocated into control (n = 50), Laughter therapy (LT) (n=50) and Humor therapy (HT) (n=50) groups. The level of Quality of life was assessed by using the WHO quality of life WHOQOL BREF scale. After the pretest, the Laughter therapy group was administered Laughter therapy and Humor therapy group received humour therapy by the researcher in addition to routine hospital care for biweekly eight sessions for both the group. The control group received routine hospital care. The data was collected at baseline, immediately after the intervention (Post-test-I) and at 3 months follow-up (Post-test-II). The results shows laughter therapy and humour therapy groups showed statistical improvement in quality of life compared to the control group at 3 months follow-up. The humour therapy improvement was better than laughter therapy in Quality of life scores. The study concludes that laughter and humour therapy is effective as complementary therapy in improving the quality of life and contributes to self-management of type 2 diabetes.